2020
DOI: 10.1111/isj.12315
|View full text |Cite
|
Sign up to set email alerts
|

Generative mechanisms of workarounds, discontinuance and reframing: a study of negative disconfirmation with consumerised IT

Abstract: This study investigates the observed behavioural outcomes when users experience negative disconfirmation with consumerised IT artefacts with the aim to identify the generative mechanisms of these outcomes. We analyse blogposts, authored and published by tablet users, where they narrate their experience with an IT artefact. We employ grounded theory method techniques, and through the lens of Critical Realism and the application of abduction and retroduction, we identify three user accommodating practices follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 127 publications
(216 reference statements)
1
25
0
Order By: Relevance
“…We adopted a partial set of GTM procedures, strictly for structuring and analysing our empirical material from the two case studies, in order to offer a rich description of the observed phenomena (Wiesche et al , 2017). We adopted Charmaz's Constructivist Grounded Theory Method (GTM) procedures for coding (Charmaz, 2006), which allowed us to use existing theories from the literature of virtual teams and the concept of perceived proximity as the “springboard” for inductive theorising (Zamani and Pouloudi, 2020, p. 12), while coding close to our data and remaining open to any emerging concepts. We used the theoretical components of perceived proximity (communication, identification) and theories such as Kolb's flow and connectivity (Kolb, 2008; Kolb et al , 2008) as sensitising devices to query our material in relation to what quality communication or increased identification may mean and how they can be achieved, having already established that Team A experiences perceived proximity, whereas Team B does not.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted a partial set of GTM procedures, strictly for structuring and analysing our empirical material from the two case studies, in order to offer a rich description of the observed phenomena (Wiesche et al , 2017). We adopted Charmaz's Constructivist Grounded Theory Method (GTM) procedures for coding (Charmaz, 2006), which allowed us to use existing theories from the literature of virtual teams and the concept of perceived proximity as the “springboard” for inductive theorising (Zamani and Pouloudi, 2020, p. 12), while coding close to our data and remaining open to any emerging concepts. We used the theoretical components of perceived proximity (communication, identification) and theories such as Kolb's flow and connectivity (Kolb, 2008; Kolb et al , 2008) as sensitising devices to query our material in relation to what quality communication or increased identification may mean and how they can be achieved, having already established that Team A experiences perceived proximity, whereas Team B does not.…”
Section: Methodsmentioning
confidence: 99%
“…inductive theorising while, at the same time, remaining open to emerging concepts and themes (Zamani & Pouloudi, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It is the magnitude and direction of disconfirmation that results in satisfaction and dissatisfaction. Positive disconfirmation results in satisfaction, while negative disconfirmation results in dissatisfaction (Venkatesh and Goel, 2010;Chen et al, 2018;Zamani and Pouloudi, 2020). The relationship between disconfirmation and satisfaction is non-symmetric.…”
Section: Service Quality Measurement: An Expectation and Desire Disconfirmation Approachmentioning
confidence: 99%
“…The EDT theory holds that consumer satisfaction is related to the magnitude and direction (positive or negative) of the discrepancies (or disconfirmation) between prior expectations and perceived performance (Churchill and Surprenant, 1982;Gorla and Somers, 2014). Three forms of disconfirmation may occur: a) expectations are confirmed when perceived performance meets expectation, b) expectations are negatively disconfirmed when perceived performance falls short of expectations, and c) expectations are positively disconfirmed when perceived performance is better than expected performance (Rouf et al, 2019;Zamani and Pouloudi, 2020).…”
Section: Introductionmentioning
confidence: 99%